Effek Ukuran Butiran Maksimum terhadap Nilai Modulus of Rupture Reactive Powder Concrete - Kushartomo, Widodo; Linggasari, Dewi; Sutandi, Arianti (Department of Civil Engineering, Diponegoro University, 2020)
Modulus of rupture (R) is a measurement of a tensile strengh of a concrete beam. The value of R is affected by the size of fine aggregat grain, the density of the concrete beam and the water-cement ratio. The unit of R is MPa expressing the tensile strength of the concrete beam without reinforcement to withstand a buckling failure. The distance between the supports of the concrete beam should not be less than three times of the height of the beam. In this research the size of the concrete beam speciment was 100 mm x 100 mm x 350 mm, the maximum fine aggregate size was varied (300 µm, 425 µm, and 600 µm) and the water-cement ratio was also varied (0.25, 0.22 and 0,20). All speciments were cured by steam curing and were tested after seven days. The results show that the larger the size of the fine aggregat grain and the higher the water-cement ratio, the smaller the R.